2019
DOI: 10.1021/acs.joc.9b00832
|View full text |Cite
|
Sign up to set email alerts
|

HBED-NN: A Bifunctional Chelator for Constructing Radiopharmaceuticals

Abstract: Radiometal-based radiopharmaceuticals bearing bifunctional HBED chelators are powerful radiotracers for cancer diagnosis and therapy. Bifunctional HBED chelators make strong complexes with trivalent gallium and are able to bind to bioactive molecules through covalent bonds. However, thus far, no bifunctional HBED chelator capable of direct conjugation via click chemistry has been reported. We hereby introduce HBED-NN as a structurally new bifunctional HBED chelator for direct click coupling. We also investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…It has been confirmed that iron depletion is an effective strategy as many studies suggest that iron overload in cells is related to the generation and development of cancer . Subsequently, chelators with hard phenolic O-donor atoms such as EHPG and HBED (Chart ) were developed for Fe 3+ chelation therapy. , Over the years, significant work across research laboratories and in clinical trials led to the development of bifunctional versions of HBED and its applications predominantly for [ 68 Ga]­Ga-based radiopharmaceuticals. …”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that iron depletion is an effective strategy as many studies suggest that iron overload in cells is related to the generation and development of cancer . Subsequently, chelators with hard phenolic O-donor atoms such as EHPG and HBED (Chart ) were developed for Fe 3+ chelation therapy. , Over the years, significant work across research laboratories and in clinical trials led to the development of bifunctional versions of HBED and its applications predominantly for [ 68 Ga]­Ga-based radiopharmaceuticals. …”
Section: Introductionmentioning
confidence: 99%
“…7 In contrast, the HBED-NN ligand facilitates convenient reaction monitoring by 1 H NMR since the sharp triazolyl singlet at 8.4 ppm (in DMSO) occurs in an uncrowded downfield region. 3 Generally, triazolyl residue protons are very sensitive to structural modification, even to quite distant changes elsewhere in the molecule to which their δ H 's respond accordingly. [3][4][5] Thus, by utilizing the proton triazolyl singlet for reaction monitoring, the conversion and chemoselectivity of chelation is able to be followed and duly optimized.…”
mentioning
confidence: 99%
“…25 The wellknown Karplus-type relationships for vicinal couplings between nuclei are functions relating 3 J's with the dihedral angles (α) between the nuclei. 26,27 They since have been developed for various systems (e.g., 25,28 however, they all exhibit quite similar trajectories, viz., 3 J is a maximum when α = 0°or 180°due to maximum overlap of orbitals and a minimum when α = 90°due to the orbitals being perpendicular to one another. The dihedral angle is not the only factor determining the size of 3 J, other factors such as bond length, order and angle as well as the presence of electronegative/positive substituents etc.…”
mentioning
confidence: 99%
See 2 more Smart Citations